Καβαλιώτες πεζογράφοι : ανθολογία μεταπολεμικής πεζογραφίας - Ζήρας, Αλέξης, 1945-; Αξιώτης, Διαμαντής (Δημοτική Βιβλιοθήκη Καβάλας, 1985)
Φώτης Πρασίνης -- Λευτέρης Νεγρεπόντης -- Βασίλης Βασιλικός -- Γιώργος Χειμωνάς -- Ιωάννης Δ. Ιωαννίδης -- Πρόδρομος Μάρκογλου -- Ηλίας Χ. Παπαδημητρακόπουλος -- Γιώργος Χουρμουζιάδης -- Σάκης Παπαδημητρίου -- Διαμάντης -- Σταύρος Βακρατσάς -- Θόδωρος Γρηγοριάδης -- Αβραάμ Χατζηανέστης